PROCESADO DE LABORATORIO PARA LA OBTENCIÓN DE LOS PARAMETROS CARACTERISTICOS DEL CORCHO EN PLANCHA - González, F; GONZÁLEZ, J R; de la Vega, R; Cristóbal, A (III Congreso Forestal Español, 2001)
We enumerate a register of trials and laboratory operations to process pluggings from probes and cork planks in general. We also set the cheracteristic parameter before and after heating and the formula to calculate them is shown
Keywords: Characteristic parameter; Cork; Quality

VARIABILIDAD DE LOS PARAMETROS CARACTERÍSTICOS DEL CORCHO EN PLANCHA CON LA ALTURA DE EXTRACCIÓN - González, F; GONZÁLEZ, J R; GARCIA DE CECA, J L; GONZÁLEZ, M (III Congreso Forestal Español, 2001)
135 cork sample planks have been gotten from 15 trees ready to uncork. Planks were taken from 5 different heights and 2 orientations. 12 variables have been measured and studied from them. The following variables show a decrease in their values with the extraction height: Yearly average growth in thickness and superficial density before and after boiling. Two groups based on the sampling average height of 130 cm can be made with the following variables: thickness expansion, visual quality and coefficient of porosity. With few exceptions, the quality index (QI) shows a bigger commercial value for the cork coming from the upper part of the debarking height
Keywords: Characteristic parameter; Cork; Quality